El Excentrico, 1973-03-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
March 20, 1973 [20 de marzo de 1973]. No volume or issue number. Cover has a photograph and reelection advertisement for San Jose councilman David Goglio.